Effect of Noise Intensity of Aviation Activities on Student Learning Concentrations - Remigius Robinson; Pujianti Bejahida Donuata; Agustinus Angelaus Ete; Muhamad Epi Rusdin (Universitas Ahmad Dahlan, 2020)
This study aims to determine the effect of flight activity noise intensity on student learning concentration. This study involved 48 students (male = 24 and female = 24) who were randomly selected in the Islamic elementary school Waioti, Maumere. The intensity of flight activity noise during classroom learning activities is measured using a Sound Level Meter (SLM), and students' concentration levels were measured using a 5-level Likert scale learning concentration questionnaire. The effect of flight noise intensity on student learning concentration was determined using linear regression analysis. The results showed that the noise level due to flight activities in the Waioti Islamic Elementary School was 58.92 dB, exceeding the set threshold value. The intensity level of students' learning concentration disorders reached 71.43%, including frequent disturbance. The level of flight activity noise significantly affects student learning concentration with the regression model: Y = 49.972 + 0.834X with R2 of 0.635.